Successful Treatment for a Large Chronic Expanding Hematoma Treated by Pneumonectomy after Arterial Embolization - Aki Fujiwara-Kuroda; null Nozomu Iwashiro; Masanori Ohara; null Kichizo Kaga (Case Reports in Pulmonology)
A chronic expanding hematoma is a rare late complication of thoracoplasty for tuberculosis, before the development of drugs. Total resection of a chronic expanding hematoma often requires invasive surgery consisting of combined resection of the lung and chest wall, accompanied by intraoperative bleeding. We report a case of successful surgical resection of a chronic expanding hematoma with preoperative arterial embolization, 48 years after extraperiosteal paraffin plombage for pulmonary tuberculosis. The operative indication or procedure for a chronic expanding hematoma should be determined carefully, and preoperative preparations as well as strategies should be elaborated for safe surgical resection. It is important to share information about treatment for a large chronic expanding hematoma, as we may continue to encounter this complication over the long term.